Analisis Kuantitatif Data Diffraksi Sinar X Fasa Keramik Crystoballite Berbasis Silika Sekam Padi dengan Metode Rietveld - Simon Sembiring (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Rietveld analysis is a means of revealing the detailed structure and composition of crystalline sample using x-ray powder diffraction data. This research presents the use of the Rietveld method using Rietica program to obtain the phase abundance of crystoballite crystal from rice husk sintered at 850oC, 950oC and 1100oC that has previously been demonstrated.The model parameters are refined by the methodof least squares until a good fit (2) to the observed data is obtained. The refined parameters in this study are background, scale factor, space groups, atom co-ordinates (U,V,W), preferred orientation, and the lattice parameters. The results showed that quantitative crystoballite crystal were 87.8, 89.8 and 98.4% weight, respectively. An acceptable result for estimation of lattice parameters and weightpercentage of crystoballite with reliability (2) was found to be < 4. The results also show that analysis by Rietveld method is efficient to control the quantity of crystoballite in the sintering process.Keywords: Rietveld, Rice Husk, X-Ray Diffraction